Classification problems of administrative documents - Майборода, Олександр Петрович (Eastern-European Journal of Enterprise Technologies, 2012)
Dividing of documents is considered by three groups. It is described, what documents can be attributed to toy or other groups. Four hierarchical levels of document of, are selected which function in establishment.